FEATURES OF THE EMOTIONAL BURNOUT CONDITION AMONG GENERAL EDUCATION SCHOOL TEACHERS - Salomova Feruza; Akhmadalieva Nigora; Sherkuziyeva Guzal; Nigmatullayeva Dilafruz (The Conference Hub, 2025)
Emotional burnout is a syndrome that arises as a result of chronic workplace stress, especially among general education school teachers. It includes three key components: emotional exhaustion, depersonalization, and reduced professional achievements. The main factors contributing to burnout are high workload, lack of support, psycho-emotional pressure, low control over work processes, and insufficient compensation. Various methods, such as surveys, stress tests, and questionnaires, are used to diagnose burnout levels. Preventing and overcoming burnout requires a comprehensive approach that includes psychological support, workload optimization, the development of a supportive work culture, and self-regulation techniques. Addressing emotional burnout among teachers contributes to improving the educational process and maintaining their professional well-being.